From the mountain to the castle : natural spaces and golden objects in Kallimachos and Chrysorrhoe - Fonseca, Rui Carlos (2020)
In this paper, I analyze the journey of three brothers told in the late Byzantine romance Kallimachos and Chrysorrhoe as well as the way in which, along their journey, natural elements and golden objects function as thresholds between human society and the supernatural world.